Long-term Outcomes of Carbon-ion Radiotherapy for Locally Advanced Squamous Cell Carcinoma of the Uterine Cervix - Okonogi, Noriyuki; Wakatsuki, Masaru; Kato, Shingo; Shiba, Shintaro; Kobayashi, Daijiro; Kiyohara, Hiroki; Karasawa, Kumiko; Ohno, Tatsuya; Nakano, Takashi; Kamada, Tadashi; Shozu, Makio (Anticancer research, 2018)
To evaluate the long-term outcomes of carbon-ion radiotherapy (C-ion RT) for locally advanced cervical squamous cell carcinoma (LAC-SqCC) in 2 prospective phase I/II studies. In the first study, 14 patients were treated with 68.8-72.8 Gy (RBE)/24 fractions. In a subsequent study, 22 patients were treated with 64.0-72.0 Gy (RBE)/20 fractions while limiting the dose to the gastro-intestinal (GI) <60 Gy (RBE). The 10-year local control rates were 92% and 61% for the patients administered a total dose of 72.0-72.8 Gy (RBE) and 64.0-68.8 Gy (RBE), respectively. Two patients in the first study developed grade 3/4 rectal or bladder complications; however, no grade 3 or higher complications occurred in the second study. C-ion RT with a higher dose was associated with excellent LC in LAC-SqCC. Long-term safety was confirmed based on the establishment of dose constraints for the GI tract.